The impact of COVID-19 on the epidemiology of non-airborne/droplet-transmitted notifiable infectious diseases in Taiwan: A descriptive study - Shun-Hsing Hung; Wei-Ting Lin; Jui-Hsiang Wang; Chih-Cheng Lai (Elsevier, 2022)
Background: This study was conducted to compare the number of cases of non-airborne/droplet-transmitted notifiable infectious disease (NID) before and after COVID-19 pandemic. Methods: This study used an open database - National Notifiable Diseases Surveillance System to collect the epidemiological data of NIDs. Ten fecal-oral-, six vector-borne-, four direct-contact, and four sexually-transmitted NIDs between pandemic period (defined as from January 2020 to December 2021) and the pre-pandemic period (defined as the period from January 2018 to December 2019) were included for the analysis. Results: Overall, the annual case number of these 24 non-airborne/droplet-transmitted NIDs was 19,186, 19,101, 19,567, and 19,863 in 2018, 2019, 2020 and 2021, respectively. The overall case number in the pandemic period was higher than those in pre-pandemic period (39,430 vs 38,287) and the monthly case number was significantly higher in pandemic period than pre-pandemic period (1643 vs 1595, p < 0.05). However, the lower case number in the pandemic period than those in pre-pandemic period was observed in overall ten fecal-oral-transmitted NIDs (1278 vs 1775), six vector-borne-NIDs (922 vs 2210), and four direct-contact transmitted NIDs (196 vs 344). In contrast, the case number of sexually-transmitted NIDs in the pandemic period was higher than those in pre-pandemic period (37,034 vs 33,958), particularly for gonorrhea (14,463 vs 8732). Conclusions: Most of the fecal-oral-, vector-borne, and direct-contact transmitted NIDs had declined during pandemic in Taiwan. In contrast, gonorrhea had large increase, and other NPIs were needed.